2011
DOI: 10.1158/1055-9965.epi-10-1153
|View full text |Cite
|
Sign up to set email alerts
|

Radon and Lung Cancer in the American Cancer Society Cohort

Abstract: Background: Case-control studies conducted in North America, Europe, and Asia provided evidence of increased lung cancer risk due to radon in homes. Here, the association between residential radon and lung cancer mortality was examined in a large-scale cohort study.Methods: Nearly 1.2 million Cancer Prevention Study-II participants were recruited in 1982. Mean countylevel residential radon concentrations were linked to study participants according to ZIP code information at enrollment [mean (SD) ¼ 53.5 Bq/m 3 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
76
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(90 citation statements)
references
References 45 publications
6
76
2
Order By: Relevance
“…Also, we used the different method for dose-response analysis based on widely accepted method in STATA software (Greenland and Longnecker, 1992). Furthermore, our result is in agreement with the recent USA cohort study where a significant positive linear trend was observed between categories of radon concentrations and lung cancer mortality (Turner et al, 2011). Although DOI:http://dx.doi.org/10.7314/APJCP.2012.13.6.2459 Residential Radon andLung Cancer Risk: An Updated Meta-analysis of Case-control Studies cohort study is more effective than case-control study, it was not included in this meta-analysis since they belong to different study designs.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Also, we used the different method for dose-response analysis based on widely accepted method in STATA software (Greenland and Longnecker, 1992). Furthermore, our result is in agreement with the recent USA cohort study where a significant positive linear trend was observed between categories of radon concentrations and lung cancer mortality (Turner et al, 2011). Although DOI:http://dx.doi.org/10.7314/APJCP.2012.13.6.2459 Residential Radon andLung Cancer Risk: An Updated Meta-analysis of Case-control Studies cohort study is more effective than case-control study, it was not included in this meta-analysis since they belong to different study designs.…”
Section: Discussionsupporting
confidence: 87%
“…Among the case-control studies included in the present meta-analysis, only the Thompson study (2008) showed a striking protective or hormetic effect on lung cancer at low radon exposure. And it is consented that to reduce residential radon to the lowest possible level would be beneficial anyhow (Turner et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Radon gas is formed during the radioactive decay of uranium-238 (2, 18,19). Radon is regarded as an independent risk factor for LC (16).…”
Section: Risk Factorsmentioning
confidence: 99%
“…Both studies were based on individual measurements (for each dwelling) of residential radon, unlike the studies having the same design and shown in Table 4 15,16,17 . In most of the latter studies, radon concentrations were obtained by estimation using mathematical models, or had measures that were directly attributable to the mean concentrations of radon in the participants' county of residence, whereas in our study, individualized radon concentrations were obtained for each dwelling 9,15,16,17 .…”
Section: Initial Cohort Cases N (%) N (%)mentioning
confidence: 99%